The Effect Of Prenatal Exercise On Sleep Quality In Pregnant Women During The Third Trimester - Marliani Marliani; Novita Sari Hasibuan; Siti Nurmawan; Feni Handayani; Ribur Sinaga; Siti Nurfadila (Open Access Health Scientific Journal, 2026)
Background: Prenatal exercise is believed to enhance third-trimester sleep quality in expectant mothers, promoting physical well-being and preparing them for childbirth. This study aimed to analyze the effect of prenatal exercise on sleep quality in pregnant women during the third trimester.Methods: This study is quantitative and quasi-experimental, employing a non-randomized one-group pretest-posttest design. This research was conducted at the Marista Sinaga Midwife Practice, Simpang Talas, Siak Regency, Riau Province, in 2024. The research was conducted in June 2024. The subjects of this research were all third-trimester pregnant women who presented for treatment at the Marista Sinaga Midwife Practice; a total of 30 participants were recruited through purposive sampling. The intervention in this study was prenatal exercise. Pre-and posttests assessing sleep quality were administered before and after the prenatal exercise. Sleep quality was measured using a questionnaire. The data analysis stage began with calculating the frequency distribution of respondent characteristics and the mean sleep quality score. Data analysis used a paired t-test because the data were normally distributed.Results: The average sleep quality score before the intervention was 3.93; after the intervention, through prenatal exercise, it increased to 8.50. Prenatal exercise significantly affected sleep quality in pregnant women in the third trimester (p = <0.001)Conclusion: Prenatal exercise significantly affects sleep quality in pregnant women in the third trimester